Tracheal agenesis: a rare congenital disorder - Dr. Ravali Gundapuneni Rao; Dr. Balaji Susarla Venkata Rama; Dr. Harshitha Gattu; Dr. Alekya Paripati (Pediatric Review: International Journal of Pediatric Research, 2021)
Tracheal agenesis is a severe congenital disorder with often an emergency presentation. There is a complete or partial absence of the trachea below the larynx, with the presence or absence of a tracheoesophageal fistula. It is a rare differential diagnosis of postnatal respiratory distress and the obstetrician or neonatologist will regularly be surprised by this malformation. The etiology of Tracheal atresia is unknown, therapeutic options are limited thus making this condition a usually fatal disorder. In most cases, congenital anomalies of the heart, digestive tract or GUT are present. The main signs are respiratory distress and cyanosis, inability to vocalize and impossible tracheal intubation. Isolated tracheal agenesis without any malformation is very rare. Here we report a case of a preterm neonate born at 33 weeks gestation with tracheal agenesis with no other associated malformation. In most cases, the seldom deformation, tracheal agenesis does not get recognized before the child is born.